Geopolityczne położenie Armenii oraz jej perspektywy po upadku Górskiego Karabachu - Kamil KŁYSZEJKO (Przegląd Geopolityczny)
The aim of the article is to explain the reasons for the fall of Nagorno-Karabakh and to indicate the geopolitical consequences of this event for Armenia itself. To this end, the author of the article presents the geopolitical position of Armenia, using Zbigniew Brzezinski's concept of the Grand Chessboard, and discusses the historical determinants of Armenia's relations with neighboring countries, as well as its demographic and military potential against the background of neighboring countries and those that exert significant influence in the region. The hypothesis of the paper is that in view of the current geopolitical situation, Armenia should deepen its cooperation with Iran, India and the United States at the expense of limiting its relations with the Russian Federation, which does not provide Armenia with security in the region anyway.